The use of search and access mechanisms to scientific articles by Brazilian researchers - Gomes, Daniel Libonati; Benchimol, Alegria Celia; Barros, Thiago Henrique Bragato [UNESP] (My University, 2018)
The present work aimed to investigate the search and access mechanisms to scientific articles most used by Brazilian researchers, covering all areas. In order to do so, a descriptive research was applied with a quantitative approach. A questionnaire was developed, which was sent to postgraduate coordinations throughout the country, so that graduate students and professors could answer it. The results showed that tool preferences tend to vary between those with more resources, the metadatabases (Google Scholar, CAPES Newspaper Portal, etc.), and those of more simplicity (generic search engines, Sci-Hub etc.), but the latter stand out in some aspects, as in the case of search by title of the article. Thus, it was concluded that, given such variety of tools, researchers tend to opt for tools that more quickly and more practically meet their needs, with the minimum of barriers to achieve what is desired, but are still reliable and ensure the relevance of the information retrieved.
O uso de ferramentas de busca e acesso a artigos acadêmicos pelos pesquisadores Brasileiros
Keywords: Academic databases; Sci-Hub; Scientific articles; Scientific communication; Search engines